Genealogi Pendidikan Riyadhah: Telaah Tafsir Pemikiran KH Hasyim Asy’ari - Muhammad Abdurrohman Al-Hadi; Khoirotul Idawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This article will elaborate on spiritual education riyadhah in the personal perspective of K.H Hasyim Asy'ari, which will be discussed based on the thoughts written in his classic works. To answer this question, the author uses primary and secondary sources. Primary sources used are taken from several book manuscripts by K.H. M. Hasyim Asy'ari. In describing them, historical interpretation techniques and meanings are needed in a deep and structured manner. In addition, secondary sources used in writing this article are books and manuscripts that support the discussion of the author's problem based on sources that have high validity. The author finds data that K.H Hasyim Asy'ari provides another dimension in discussing, applying and practicing spiritual education values including through riyadhah. Riyadhah education is presented with a simple concept that is in accordance with Islamic teachings based on thoughts in the form of implementation of narratives and writings of his works with implied or explicit messages.